Rapid detection of β-lactamase activity using the rapid Amp NP test - Patrice Nordmann; Nicolas Helsens; Nicolas Kieffer; Camille Tinguely; Gilbert Greub; Laurent Poirel (Microbiology Spectrum)
ABSTRACT Urinary tract infections (UTIs) are the most common bacterial infections in humans. They are mainly caused by Escherichia coli and other Enterobacterales for which increasing resistance to antibiotics and in particular to β-lactams is extensively reported. The detection of β-lactam resistance phenotypes is currently time-consuming (18 h). Hence, most treatments are given without any results of antibiotic susceptibility testing and may involve broad-spectrum antibiotics. A biochemical diagnostic test has been developed to rapidly evaluate the production of β-lactamases (and consequently the β-lactam resistance) from cultures (104 and 105 CFU/mL) of Gram-positive and Gram-negative isolates representative of bacterial species as a source of UTIs (n = 112). It relies on a centrifugation step after a 90 min preliminary culture and the detection of β-lactamase activity with nitrocefin as substrate using a special filter. Overall, the test gave a positive result for 87.6% of the tested resistant strains with a bacterial load of 105 CFU/mL, and a positive result for 100% of tested extended-spectrum β-lactamases and for carbapenemase producers at the same load. This cost-effective test can be performed in any laboratory and ultimately shall be tested at the patient side and at the general practitioner. Its turn-around-time to get results is less than 2 h. After further improvements, the results obtained with this proof-of-concept test suggest that its use may contribute to rapidly guide the treatment of non-complicated UTIs and, therefore, limit the use of broad-spectrum antibiotics and the emergence of antibiotic resistance.IMPORTANCEThis work reports on a totally novel diagnostic technique, the Rapid Amp NP test for the identification of amoxicillin/ampicillin resistance in bacteria that are sources of non-complicated urinary tract infections. Those preliminary results obtained with cultured bacteria are promising. We believe its future use may contribute to reconsider aminopenicillins as a first line therapy for treating UTI infections. The corresponding patent of this test obtained both for the United States and Europe may contribute to its further industrialization.